Body mass index and serum levels of soluble leptin receptor are sex-specifically related to alcohol binge drinking behavior - Bouna-Pyrrou, Polyxeni; Muehle, Christiane; Kornhuber, Johannes; Weinland, Christian; Lenz, Bernd (Psychoneuroendocrinology, 2021)
Objective - Binge drinking is a highly prevalent behavior in adolescents and young adults and a risk factor to develop alcohol use disorder. Body mass index (BMI) and blood levels of leptin peptide and its soluble receptor have been implicated in alcohol use disorder; however, their role in binge drinking remains to be investigated. - Method - We studied associations of BMI, serum levels of soluble leptin receptor (ObRe) and leptin as well as the free leptin index with binge drinking in 93 male and 99 female young adults. - Results - In men, binge drinkers showed significantly higher BMI (kg/m2) than non-binge drinkers (23.67 vs. 22.08) and higher BMI correlated significantly with more severe binge drinking episodes (ρ = 0.251). In women, we found significantly higher ObRe (ng/ml) / BMI (kg/m2) values in binge drinkers than in non-binge drinkers (0.52 vs. 0.44) and ObRe/BMI values correlated significantly with more severe binge drinking episodes (ρ = 0.210). - Conclusion - This study confirms that higher BMI associates with binge drinking in men and shows for the first time a role of ObRe/BMI in binge drinking in women. Our data emphasize the importance of further research in the ﬁeld of metabolic markers and implications in neurobiological processes of binge drinking.